Preplant Soil Assessment for New Residential Landscapes in Florida - Amy L. Shober; Christine Wiese (EDIS, 2010)
SL322, a 5-page illustrated fact sheet by Amy L. Shober and Christine Wiese, advocates performing an assessment of soil conditions before landscape installation, and outlines the issues that may be identified through such an assessment. Includes references. Published by the UF Department of Soil and Water Science, June 2010.